Neotype designation and re-description of Forsskål’s reticulate whipray Himantura uarnak - (:unkn) unknown (My University, 2021)
A continuing impediment to the taxonomy of the reticulate whipray Himantura spp. species complex is the absence of a type specimen for H. uarnak (Gmelin [ex Forsskål], 1789). Here, reticulate whipray specimens were sampled from the Jeddah region in the Red Sea, the assumed type locality of H. uarnak, and characterized genetically at the cytochrome-oxidase subunit 1 (CO1) locus. One of these specimens now in the fish collection of the California Academy of Sciences was designated as neotype. The maximum-likelihood phylogeny of all available CO1 gene sequences from the genus Himantura had the following topology: ((H. leoparda, H. uarnak), (H. undulata, (Himantura sp. 2, (H. australis + Himantura sp. 1))), H. tutul), where H. uarnak haplotypes formed a distinct lineage sister to H. leoparda. Based on these CO1 gene sequences, the geographic distribution of H. uarnak includes the eastern Mediterranean, the Red Sea, the East African coast, and the Arabian Sea. At least one lineage in the reticulate whipray species complex remains to be named.
Keywords: African Research